2005
DOI: 10.1177/016264340502000202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-Based Cognitive Mapping on Reading Comprehension for Students with Emotional Behavior Disorders

Abstract: Three students with behavior disorders who exhibited difficulty with reading in content area courses learned to use a computer program to create cognitive maps of the reading material required for class. Using a modified multiple-probe design across behaviors or stimulus sets, replicated across students, allowed for the evaluation of student performance on written and oral quizzes covering content area information. All students improved reading comprehension of content material with this intervention, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 8 publications
(9 reference statements)
0
56
0
Order By: Relevance
“…However, the effectiveness of hypermedia enhancements over an extended period of time cannot be determined due to the short duration of this study. Blankenship, Ayers, and Langone (2005) studied the effect of computer-based cognitive mapping on reading comprehension of three 9th graders with EBD. The students used the computer program Inspiration for creating cognitive maps of the material they read.…”
Section: Readingmentioning
confidence: 99%
“…However, the effectiveness of hypermedia enhancements over an extended period of time cannot be determined due to the short duration of this study. Blankenship, Ayers, and Langone (2005) studied the effect of computer-based cognitive mapping on reading comprehension of three 9th graders with EBD. The students used the computer program Inspiration for creating cognitive maps of the material they read.…”
Section: Readingmentioning
confidence: 99%
“…Fitzgerald (2005) found that the use of technology in the classroom environment related to core subject areas resulted in higher academic performance on outcome measures and higher perception of engagement on the part of the teacher. Blankenship, Ayres, and Langone (2005) found that the use of computer-based cognitive mapping resulted in substantial increases in students reading comprehension levels after intervention. With the lack of engagement of students with EBD being correlated to a lack of academic achievement , technology may be a variable that can increase student engagement with school, eventually leading to higher outcomes (Cumming et al, 2008;Fitzgerald, 2005).…”
Section: Emotional and Behavioral Disordersmentioning
confidence: 94%
“…Students and teacher then discuss how the nodes might relate to one another, creating super-and subordinate concepts and linking ideas together, which can be done "on the fly." Several studies have shown that student-generated concept mapping, based on social studies textbook passages, improves the retention and comprehension of students with disabilities (Blankenship, Ayers, & Langone, 2005;Boon, Burke, Fore, & Hagen-Burk, 2006;Boon, Burke, Fore, & Spencer, 2006;Boon, Fore, Ayers, & Spencer, 2005).…”
Section: Graphic Organizersmentioning
confidence: 99%